Brachial flow-mediated vasodilator responses in population-based research: methods, reproducibility and effects of age, gender and baseline diameter. - Herrington, D M; Fan, L; Drum, M; Riley, W A; Pusser, B E; Crouse, J R; Burke, G L; McBurnie, M A; Morgan, T M; Espeland, M A (J Cardiovasc Risk, 2001)
BACKGROUND: Brachial artery ultrasound has been proposed as an inexpensive, accurate way to assess cardiovascular risk in populations. However, analysis and interpretation of these data are not uniform. METHODS: We analysed the relationship between relative and absolute changes in brachial artery diameter in response to flow-mediated dilation and age, gender and baseline diameter among 4,040 ultrasound examinations from subjects aged 14 to 98 years. RESULTS: Reproducibility studies demonstrated intra- and interreader and intrasubject correlations from 0.67 to 0.84 for repeated measures of per cent change in diameter. Per cent change in diameter after flow stimulus was 3.58 +/- 0.10% (mean +/- standard deviation). Corresponding values for baseline diameter and absolute change in diameter were 4.43 +/- 0.87 mm and 0.15 +/- 0.01 mm, respectively. Baseline diameter and its variance were inversely related to per cent change in diameter (P< 0.001). In contrast, absolute change in diameter was more uniform throughout the range of baseline diameters. Baseline diameter was directly related, and per cent change in diameter inversely related, to age (P < 0.001 for all three measures). Time to maximum vasodilator response increased with age (P < 0.001). Women (n=2,315) had significantly larger per cent change in diameter than men (n=1,725) (P < 0.001). However, after adjustment for age and baseline diameter, per cent and absolute change were 5% smaller in women than men (P < 0.05 for both). In multivariate analysis, age was overwhelmingly the most important determinant of absolute change in diameter (P < 0.001). CONCLUSIONS: Automated analysis of brachial flow-mediated vasodilator responses is both feasible and reproducible in large-scale clinical and population-based research.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Blood Circulation; Brachial Artery; Female; Humans; Male; Middle Aged; Observer Variation; Population Surveillance; Reproducibility of Results; Sex Factors; Vasodilation; Vasodilator Agents